2009
DOI: 10.1128/jb.01695-08
|View full text |Cite
|
Sign up to set email alerts
|

BldG and SCO3548 Interact Antagonistically To Control Key Developmental Processes inStreptomyces coelicolor

Abstract: The similarity of BldG and the downstream coexpressed protein SCO3548 to anti-anti-sigma and anti-sigma factors, respectively, together with the phenotype of a bldG mutant, suggests that BldG and SCO3548 interact as part of a regulatory system to control both antibiotic production and morphological differentiation in Streptomyces coelicolor. A combination of bacterial two-hybrid, affinity purification, and far-Western analyses demonstrated that there was self-interaction of both BldG and SCO3548, as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…Interestingly, in contrast to ApgA, which formed a complex with BldG at an ϳ1:1 molar ratio, UshX and BldG have been found to form a complex at an ϳ1:2 molar ratio. The 1:1 molar ratio of the ApgA-BldG complex is consistent with the proposed heterotetrameric complex consisting of an ApgA dimer interacting with a BldG dimer (43). Assuming that BldG forms a dimer, it is likely that it may interact with one molecule of UshX.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Interestingly, in contrast to ApgA, which formed a complex with BldG at an ϳ1:1 molar ratio, UshX and BldG have been found to form a complex at an ϳ1:2 molar ratio. The 1:1 molar ratio of the ApgA-BldG complex is consistent with the proposed heterotetrameric complex consisting of an ApgA dimer interacting with a BldG dimer (43). Assuming that BldG forms a dimer, it is likely that it may interact with one molecule of UshX.…”
Section: Resultssupporting
confidence: 59%
“…BldG has also been found to interact with another antisigma factor homologue, ApgA (SCO3548) (43), as verified also by our results. Based on these results, BldG has several anti-sigma partners to regulate, and in addition to H , likely also other B homologues, as H does not interact with the other BldG-specific anti-sigma factor, ApgA (Fig.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…An anti-sigma factor RsbA (SCO0599) with an anti-anti-sigma factor RsbV (SCO7325) has been shown to be involved in osmotic stress activation of σ B (Lee et al, 2004a), an anti-sigma factor RsmA (SCO7313) regulates the activity of σ M (Gaskell et al, 2007), an anti-sigma factor RsfA has been found to interact with σ F and two homologues for antianti-sigma factors, SCO0781 and SCO0869 (Kim et al, 2008), and an anti-anti-sigma factor BldG (SCO3549) has been shown to be involved in osmotic stress activation of σ H , through sequestering its anti-sigma factor UshX/PrsH (SCO5244) (Sevcikova et al, 2010). The regulation seems to be more complex, as BldG has been shown to interact with an anti-sigma factor ApgA (Parashar et al, 2009;Sevcikova et al, 2010).…”
Section: Introductionmentioning
confidence: 96%